2006
DOI: 10.1021/om060359h
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Olefin Hydrosilylation Catalyzed by RuCl2(CO)2(PPh3)2: A DFT Study

Abstract: Density functional theory (DFT) was used to explore the different mechanistic possibilities for the hydrosilylation reaction between methyldimethoxysilane and methylvinyldimethoxysilane catalyzed by the Ru(II) complex dicarbonyldichlorobis(triphenylphosphine)ruthenium(II) (A1). Reaction enthalpy profiles of the Chalk-Harrod, modified Chalk-Harrod, and σ-bond metathesis mechanisms were computed for several different active forms of A1. A total of 10 different pathways with different catalytic cycles and differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 71 publications
(95 reference statements)
4
51
0
Order By: Relevance
“…Sakaki et al, elucidated the RhCl(PH 3 ) 3 -catalyzed hydrosilylation obey the modified Chalk-Harrod mechanism [30]. Alternatively, the r-bond metathesis mechanism [31], in which a initial formed MAC bond is cleaved by a SiAH bond of uncoordinated silane via the four-membered transition state to afford MAH and CASi bonds simultaneously, has been considered for the Ru-catalyzed hydrosilylation of alkenes [32,33] and the ethylene hydrosilylation catalyzed by ZrCp 2 [34] and bis-N-heterocyclic carbene rhodium complex [35]. In addition, Beddie and Hall [36] provided the first theoretical evidence for the Glaser-Tilley mechanism [7] involving the direct insertion of alkene into the SiAH bond of ruthenium silylene complex without direct interaction between the alkene and metal center.…”
Section: Introductionmentioning
confidence: 99%
“…Sakaki et al, elucidated the RhCl(PH 3 ) 3 -catalyzed hydrosilylation obey the modified Chalk-Harrod mechanism [30]. Alternatively, the r-bond metathesis mechanism [31], in which a initial formed MAC bond is cleaved by a SiAH bond of uncoordinated silane via the four-membered transition state to afford MAH and CASi bonds simultaneously, has been considered for the Ru-catalyzed hydrosilylation of alkenes [32,33] and the ethylene hydrosilylation catalyzed by ZrCp 2 [34] and bis-N-heterocyclic carbene rhodium complex [35]. In addition, Beddie and Hall [36] provided the first theoretical evidence for the Glaser-Tilley mechanism [7] involving the direct insertion of alkene into the SiAH bond of ruthenium silylene complex without direct interaction between the alkene and metal center.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study [19], this reaction was found to have a prohibitively high barrier (DH act = 53.6 kcal/mol) and a catalyst is therefore needed to lower the activation enthalpy for the hydrosilylation to occur under normal operating conditions.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, it has also been shown to be active in a number of late transition metal catalysts as well [19,[41][42][43][44][45][46][47][48][49][50][51]. Finally, in 2003, Glaser and Tilley proposed another mechanism for a cationic silylene Ru(II) catalyst in the hydrosilylation of alkenes [11], and subsequent computational studies supported this proposal [10].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It should be noted here that the entropic contribution to the free energies based on the gasphase calculations is overestimated for those steps involving substrate association or dissociation. Recent discussions on the overestimation can be found in the literature [48,49]. …”
Section: Computational Detailsmentioning
confidence: 99%